Ruling Family Political Connections and Risk Reporting: Evidence from the GCC - Al-Hadi, Al-Hadi Ahmed; Taylor, Grantley; Al-Yahyaee, K. (2016)
© 2016 University of IllinoisThis study examines whether the presence of ruling family members on boards of directors influences the extent and the quality of risk reporting. Based on a sample of publicly listed financial firms of the Gulf Cooperation Council countries between 2007 and 2011, our regression results show that ruling family board members reduce the quality and extent of risk disclosures. Firms with ruling family board members also disclose significantly less during periods of financial distress and when they are subject to higher levels of risk. We find that risk reporting is negatively associated with the existence of a ruling family director acting as the board chairperson, negatively associated with increasing proportions of ruling family directors on the board, and negatively associated with increasing numbers of board members who are connected to ruling family directors. Our results suggest that politically connected directors seize private benefits at the expense of their firms' shareholders. Our regression results hold after a series of robustness checks that control for endogeneity and for alternative measures of ruling family membership.